IRE1-mTOR-PERK Axis Coordinates Autophagy and ER Stress-Apoptosis Induced by P2X7-Mediated Ca2+ Influx in Osteoarthritis - Li, Zihao; Huang, Ziyu; Zhang, He; Lu, Jinghan; Wei, Yingliang; Yang, Yue; Bai, Lunhao (Frontiers in Cell and Developmental Biology, 2021)
Moderate-intensity exercise can help delay the development of osteoarthritis (OA). Previous studies have shown that the purinergic receptor P2X ligand gated ion channel 7 (P2X7) is involved in OA development and progression. To investigate the effect of exercise on P2X7 activation and downstream signaling in OA, we used the anterior cruciate ligament transection (ACLT)-induced OA rat model and primary chondrocyte culture system. Our in vivo experiments confirmed that treadmill exercise increased P2X7 expression and that this effect was more pronounced at the later time points. Furthermore, P2X7 activation induced endoplasmic reticulum (ER) stress and increased the expression levels of ER stress markers, such as 78 kDa glucose-regulated protein (GRP78), protein kinase R-like endoplasmic reticulum kinase (PERK), inositol-requiring enzyme-1 (IRE1), and activating transcription factor 6 (ATF6). At the early time points, IRE1 and PERK were activated, and mTOR was inhibited. At the later time points, mTOR was activated, mediating PERK to promote ER stress-apoptosis, whereas IRE1 and autophagy were inhibited. To confirm our observations in vitro, we treated primary chondrocytes with the P2X7 agonist benzoylbenzoyl-ATP (Bz-ATP). Our results confirmed that P2X7-mediated Ca2+ influx activated IRE1-mediated autophagic flux and induced PERK-mediated ER stress-apoptosis. To further investigate the role of P2X7 in OA, we injected mTOR antagonist rapamycin or P2X7 antagonist A740003 into the knee joints of ACLT rats. Our results demonstrated that mTOR inhibition induced autophagy, decreased apoptosis, and reduced cartilage loss. However, injection of mTOR agonist MHY1485 or Bz-ATP had the opposite effect. In summary, our results indicated that during the early stages of moderate-intensity exercise, P2X7 was activated and autophagic flux was increased, delaying OA development. At the later stages, P2X7 became over-activated, and the number of apoptotic cells increased, promoting OA development. We propose that the IRE1-mTOR-PERK signaling axis was involved in the regulation of autophagy inhibition and the induction of apoptosis. Our findings provide novel insights into the positive and preventative effects of exercise on OA, suggesting that the intensity and duration of exercise play a critical role. We also demonstrated that on a molecular level, P2X7 and its downstream pathways could be potential therapeutic targets for OA.